2011
DOI: 10.1016/j.bbrc.2011.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia telangiectasia mutated influences cytochrome c oxidase activity

Abstract: Cells lacking ataxia telangiectasia mutated (ATM) have impaired mitochondrial function. Furthermore, mammalian cells lacking ATM have increased levels of reactive oxygen species (ROS) as well as mitochondrial DNA (mtDNA) deletions in the region encoding for cytochrome c oxidase (COX). We hypothesized that ATM specifically influences COX activity in skeletal muscle. COX activity was ~40% lower in tibialis anterior from ATM-deficient mice than for wildtype mice (P<0.01, n=9/group). However, there were no ATM-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 27 publications
3
22
0
1
Order By: Relevance
“…46 Levels of complex I and ATP were also significantly decreased in the ATM-deficient thymocytes 46 ; in turn, these findings were consistent with those of previous studies showing that the activities of complex I and complex IV (cytochrome c oxidase) in mitochondria of ATMdeficient mice were greatly diminished in skeletal muscle and liver extracts, respectively. 92,93 It is interesting that Valentin-Vega et al 46 showed that the abnormally high mitochondrial mass, elevated mitochondrial respiration rates, and mitochondrial complex I deficiency in Atm 2/2 thymocytes could all be reversed when these cells were made heterozygous for the Beclin-1 gene, which encodes the Beclin-1 protein regulator of autophagy. It should be recognized, however, that the mechanisms by which Beclin-1 regulates mitochondrial biogenesis, as well as complexes of the mitochondrial ETC/OXPHOS system and respiration rates, require further elucidation.…”
Section: Atm and Mitochondriamentioning
confidence: 99%
“…46 Levels of complex I and ATP were also significantly decreased in the ATM-deficient thymocytes 46 ; in turn, these findings were consistent with those of previous studies showing that the activities of complex I and complex IV (cytochrome c oxidase) in mitochondria of ATMdeficient mice were greatly diminished in skeletal muscle and liver extracts, respectively. 92,93 It is interesting that Valentin-Vega et al 46 showed that the abnormally high mitochondrial mass, elevated mitochondrial respiration rates, and mitochondrial complex I deficiency in Atm 2/2 thymocytes could all be reversed when these cells were made heterozygous for the Beclin-1 gene, which encodes the Beclin-1 protein regulator of autophagy. It should be recognized, however, that the mechanisms by which Beclin-1 regulates mitochondrial biogenesis, as well as complexes of the mitochondrial ETC/OXPHOS system and respiration rates, require further elucidation.…”
Section: Atm and Mitochondriamentioning
confidence: 99%
“…Recently, ATM was found to regulate the levels of reactive oxygen species (ROS) in mammalian cells (6) but the source of this ROS remains unclear. Although mitochondrial leakage has been suggested as the primary ROS source, other work indicates that alternative uncharacterized sources may be important (7).…”
mentioning
confidence: 99%
“…Moreover A-T cells have lower cytochrome c oxidase activity than normal cells, which could explain their reduced respiratory activity; interestingly, treatment of normal cells with an ATM inhibitor also results in reduced cytochrome c oxidase activity [50]. While there are numerous external sources of ROS, the great majority of ROS within eukaryotic cells derives from the mitochondrion as by-products during the generation of adenosine triphosphate (ATP), through the process of oxidative phosphorylation.…”
Section: Atm and Mitochondriamentioning
confidence: 99%